Anyang Public Art Project 2007 - Anyang Public Art Project Foundation, Anyang; Gautherot, Franck; Kim Seung-Duk; Sung Won Kim (Anyang : Anyang Public Art Project Foundation Anyang, 2007)
Armleder, John ; Bul, Lee ; Bulloch, Angela ; Buren, Daniel ; Chaimowicz, Marc Camille ; Elmgreen & Dragset ; Eunji Cho ; Feinstein, Rachel ; Fleury, Sylvie ; Flyingcity ; Friedmann, Gloria ; Gillick, Liam ; Gimhongsok ; Graham, Dan ; Han Jung-Wan ; In-Dong LIM ; Kim Sanggyun ; Kusama Yayoi ; Lavier, Bertrand ; Lee Mi Kyeong ; Lester, Gabriël ; Lim Minouk ; Löbbert, Maik & Dirk ; M/M (Paris) ; Mosset, Olivier ; Nakamura, Masato ; Nayoungim ; Oak Jung Ho ; Oh Inhwan ; Park Kyung-Jin ; Park MeeNa ; Park Shin-Ja ; Park Soyoung ; Pernice, Manfred ; Perret, Mai-Thu ; Rehberger, Tobias ; Rho Jae Oon ; Shin Hyungsub ; Sookyung Yee ; Sulki & Min ; Tiravanija, Rirkrit ; Webb, Gary ; Weiner, Lawrence ; Woo Bo-Hyong ; Yan Pei-Ming ; Yang Haegue
biog. p. 291-302
Engels
Koreaans
Published on the occasion of the exhibition 'Anyang Public Art Project 2007' at Anyang, 20.10.2007
boek